AB0936 Golimumab improves disease signs and symptoms, concomitant diseases and concomitant drug use in patients with psoriasis arthritis in a real-life setting in germany. (12th June 2018) - Krüger, K.; Burmester, G.R.; Wassenberg, S.; Thiele, A.; Thomas, M.H.
Abstract : Background: Golimumab (GLM) has demonstrated efficacy and safety in several randomised clinical trials in Psoriatic Arthritis (PsA) patients. Data on disease signs and symptoms, concomitant diseases and concomitant drug in daily clinical practice are rare Objectives: The aim of this subanalysis was to assess the effectiveness of GLM in patients with established PsA in a real-world setting in Germany Methods: Descriptive post-hoc analysis of the non-interventional, prospective, 24 month study GO-NICE. Patients with established PsA starting with GLM 50 mg SC once monthly under routine clinical care conditions. Endpoint measures were: Physician's Global Assessment (PhGA) of patient's health status (visual analogue scale VAS: 0 no discomfort – 10 strong discomfort), change in concomitant diseases, concomitant drug use, inflammatory markers (CRP/ESR), improvement of the skin (PhGA-score: 0=none – 3=severe). Results: A total of 501 patients with PsA were included at 121 sites and 231 (46.1%) completed the 24 month observation period. At baseline (BL) mean age 50.3 (±12.1) years, 271 (54.1%) females, mean time since first diagnosis 13.0±11.5 years, BMI 28.1 (±5.4) kg/m 2 . 169 (73.8%) patients received basic therapeutics, 286 (57.1%) had none previous biologics use, 136 (27.1%) one, and 79 (15.8%) at least two biologics. 439 (87.8%) had extra-articular diseases manifestations at BL. The most common were psoriasis (n=394, 78.8%), nail involvement (n=197, 39.4%), dactylitis (n=106, 21.2%), and enthesitis (70, 14.0%) at BL. The three most concomitant diseases were cardiovascular disease (n=151, 30.1%), depressive disorder (n=60, 12.0%), and diabetes mellitus (n=52, 10.4%). On GLM treatment, remarkable improvements were seen (table 1): Additionally, the percentage of patients with severe psoriatic symptoms decreased from 11.8% (BL) to 1.8% (M12) to 0.4% (M24), and the percentage of patient without any symptom increased from 8.8% (BL) to% 31.8 (M12) to 36.2% (M24). An increase in any of the prespecified concomitant diseases was not observed. No new safety signals were detected. Conclusions: GLM SC once-monthly, administered to PsA patients according to routine clinical practice in Germany, showed remarkable improvements in Physician's Global Assessment of patient's health status, decrease in the number of concomitant diseases and concomitant glucocorticoids use, inflammatory markers (CRP/ESR) and skin symptoms over 24 months of treatment. Disclosure of Interest: K. Krüger Consultant for: AbbVie, BMS, Celgene, Janssen Biologics, Lilly, MSD, Pfizer, Roche, and Sanofi-Aventis, and UCB, G. Burmester Consultant for: AbbVie, BMS, MSD, Pfizer, Roche, and UCB, S. Wassenberg Consultant for: AbbVie, Chugai, Janssen Biologics, MSD, Novartis, Pfizer, Roche, and UCB, A. Thiele Consultant for: Biogen, Celgene, Chugai, Hexal, Janssen-Cilag, Lilly, MSD, Novartis, Pfizer, UCB, M. Thomas Employee of: MSD Sharp and Dohme GmbH